2020
DOI: 10.1101/2020.07.20.211409
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Activation of a neural stem cell transcriptional program in parenchymal astrocytes

Abstract: Neural stem cells, located in discrete niches in the adult brain, generate new neurons throughout life. These stem cells are specialized astrocytes, but astrocytes in other brain regions do not generate neurons under physiological conditions. After stroke, however, striatal astrocytes undergo neurogenesis in mice, triggered by decreased Notch signaling. We used single-cell RNA sequencing to characterize neurogenesis by Notch-depleted striatal astrocytes in vivo. Striatal astrocytes were located upstream of neu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…To ask whether fundamental environmental differences affect neuronal reprogramming efficiency, we isolated astrocytes and cultured them in the continuous presence of FGF2 and EGF. By this growth factor treatment alone, a small percentage of bIII-tubulin + cells among control virus-infected cells appeared (Figures 3A and 3C), probably because FGF2 and EGF can confer stem cell-like properties on astrocytes, enabling them to differentiate into neurons in accordance with previous reports (Kleiderman et al, 2016;Magnusson et al, 2020). In addition, unlike in the absence of these growth factors (Figures 2C and 2D), we found that even a single NeuroD1 virus infection together with FGF2 and EGF could effectively induce AtN conversion by 7 dpt (Figures 3B and 3C).…”
Section: Differences In Cell Context Affect Neuronal Reprogramming Efficiencysupporting
confidence: 90%
“…To ask whether fundamental environmental differences affect neuronal reprogramming efficiency, we isolated astrocytes and cultured them in the continuous presence of FGF2 and EGF. By this growth factor treatment alone, a small percentage of bIII-tubulin + cells among control virus-infected cells appeared (Figures 3A and 3C), probably because FGF2 and EGF can confer stem cell-like properties on astrocytes, enabling them to differentiate into neurons in accordance with previous reports (Kleiderman et al, 2016;Magnusson et al, 2020). In addition, unlike in the absence of these growth factors (Figures 2C and 2D), we found that even a single NeuroD1 virus infection together with FGF2 and EGF could effectively induce AtN conversion by 7 dpt (Figures 3B and 3C).…”
Section: Differences In Cell Context Affect Neuronal Reprogramming Efficiencysupporting
confidence: 90%
“…This may be a The transition of EpA cells from a highly differentiated ependymal cell state to a stem-cell-like state and their generation of other differentiated cells after injury is reminiscent of the process in which parenchymal astrocytes gives rise to new neurons after a stroke. After a striatal stroke, local astrocytes undergo similar transcriptional changes as we describe here for EpA cells to reach a stem-cell-like state before initiating neurogenesis (Magnusson et al, 2014(Magnusson et al, , 2020. This latent stem cell potential of some differentiated glial cells appears to be evolutionarily conserved, but with a much more limited role in regeneration in the adult mammalian central nervous system.…”
Section: Discussionmentioning
confidence: 53%
“…S1). As previously described, homozygous deletion of RBPj-κ (RBPj-κ fl/fl ) induced a neurogenic program in medial striatal astrocytes, which led to the upregulation of the proneural transcription factor Ascl1, proliferation and the generation of neuroblasts, which consequently mature into NeuN + neurons (15,18) (Fig. 1A).…”
Section: Significancementioning
confidence: 66%
“…In mice, adult striatal neurogenesis occurs in response to striatal lesions, indicating a role in the endogenous repair process. Following a lesion to the striatum, Notch signaling is downregulated in local astrocytes, which induces their recruitment into a neurogenic program (15,18). Here, we took advantage of this mechanism to generate adult-born, astrocyte-derived, striatal neurons in the uninjured mouse striatum by genetic deletion of the Notch effector RBPj-κ in astrocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation